2009
DOI: 10.1117/12.829619
|View full text |Cite
|
Sign up to set email alerts
|

Flexible radiation dosimeters incorporating semiconducting polymer thick films

Abstract: Flexible radiation dosimeters have been produced incorporating thick films (>1 μm) of the semiconducting polymer poly([9,9-dioctylfluorenyl-2,7-diyl]-co-bithiophene). Diode structures produced on aluminium-metallised poly(imide) substrates, and with gold top contacts, have been examined with respect to their electrical properties. The results suggest that a Schottky conduction mechanism occurs in the reverse biased diode, with a barrier to charge injection at the aluminium electrode. Optical absorption/emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…[12] Although these organic materials can be susceptible to radiation damage, [13] they have some advantages for their use as X-ray detectors, such as mechanical flexibility, tissue equivalence, and an ability to be coated over large areas. [13,14] We have previously produced X-ray induced photocurrents (on the order of ten nA) in several micrometer thick semiconducting polymer films exposed to incident 17.5 keV Xray doses of up to 70 mGy.s -1 . [11,14] As the dark current produced by these devices is approximately 0.1 nA, the X-ray induced photocurrent can be detected in laboratory applications using sensitive ammeters and electrical amplifiers.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Although these organic materials can be susceptible to radiation damage, [13] they have some advantages for their use as X-ray detectors, such as mechanical flexibility, tissue equivalence, and an ability to be coated over large areas. [13,14] We have previously produced X-ray induced photocurrents (on the order of ten nA) in several micrometer thick semiconducting polymer films exposed to incident 17.5 keV Xray doses of up to 70 mGy.s -1 . [11,14] As the dark current produced by these devices is approximately 0.1 nA, the X-ray induced photocurrent can be detected in laboratory applications using sensitive ammeters and electrical amplifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, direct detection of electron [13] and alpha (α) particles [14,15] has been achieved using polymers as the active layer. We have recently shown that direct X-ray induced photocurrents can be observed in metal/semiconducting polymer/metal diode structures [7,8,16,17] indicating the feasibility of using conjugated polymers in direct real-time radiation detection applications. The addition of small organic semiconducting molecules to Published in Nanotechnology 23 (2012) 235502 4 the polymer increased the charge-carrier mobility, which resulted in increased X-ray sensitivities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous electronic devices, including field effect transistors [1], light-emitting diodes [2], photovoltaic cells [3], and radiation sensors [4,5], have in recent years employed organic materials as the active component. These devices share one common feature in that their efficiency depends strongly on the transport of charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymers -in the place of conventional inorganic semiconductors -opens up the possibility for large-area fabrication of sensors using low-cost, wet processing techniques, Published in Organic Electronics (2011) 12, 1903-1908 3 such as spin-casting, spray-casting, ink-jet or roll-to-roll printing [17]. Radiation sensors made from polymers exhibit greater mechanical flexibility in comparison to inorganic solids [5]. Furthermore, the elemental composition of most polymers (C, H, N and O) makes them an ideal candidate for dosimeters in medical applications, in which the detector requires a "human tissue-equivalent" interaction with radiation.…”
Section: Introductionmentioning
confidence: 99%